Perbuatan Melawan Hukum terhadap Sengketa Kepemilikan Hak Atas Tanah Masyarakat Adat - Ririh Titis Yusriyyah; Zakki Adlhiyati (Universitas Sebelas Maret, 2024)
This article analyzes the tort of dispute over ownership of land rights located on customary land. The purpose of this article is to determine the unlawful acts against the law on disputes over ownership of land rights of indigenous peoples by examining the Decision of the Judge of the Kolaka District Court Number 31/Pdt.G/2021/PN Kka. The research method used is doctrinal or normative legal research. This research is descriptive in nature. The method of collecting legal materials by means of library research or document studies and legal materials used are primary and secondary legal materials. The results of this study discuss the customary law of land tenure in the Tolaki-mekongga indigenous community based on clearing forests, inheriting (Tiari), gifts or gifts of people (Pomboweehinotono), expiration (Puta), legal purchase (Mo'oli). Land tenure without these five methods is illegal because it has violated applicable customary law. Based on the results of research and discussion to answer the problem, it can be concluded that the unlawful act in the Kolaka District Court Decision Number 31/Pdt.G/2021/PN Kka regarding unlawful acts related to ownership of Kolaka customary land is a unlawful act categorized as unlawful acts against decency.